Magnetic materials and devices - Varun Chaudhary; R Nirmala; Yulong Huang (Materials Research Express)
Magnetic materials are omnipresent in everyday life, with applications spanning a wide range of fields. This focus collection provides a comprehensive overview of recent developments in the synthesis and characterization of advanced magnetic materials, both in their bulk and low-dimensional forms. These studies aim to enhance our understanding of fundamental physical properties and identify suitable candidate materials for various device applications. We believe that this focus collection will serve not only as a valuable reference but also as a source of inspiration for further research on advanced magnetic materials.